Particularities of dental medical services and consumers in the context of globalization - GEANGU, Petronela Iuliana; CREŢOIU, Raluca; GÂRDAN, Daniel Adrian (Annals of Spiru Haret University. Economic Series, 2011)
Globalization determines a growth of competition but as well a growth of the opportunity to attract new customers. The dental clinics will have to keep in mind the new characteristics and features of the modern consumer who is more educated, more informed, more active in searching for products and services, more communicative with the providers and the other consumers and more inclined to the cognitive side. At the same time, although they have to admit the traits of the new type of consumer – for whom there are no borders, the clinics must perform marketing researches and be permanently connected to each patient in order to be aware of the particularities of the local communities and even of the individual traits because the present consumer is more demanding and wants unique non-repetitive consumption experiences. For a dental clinic, the globalization supposes a global thinking and global action, not the homogenization of products and services they offer, as well as considering their hybridization, especially from the cultural point of view.